Importance of access to epilepsy monitoring units during the COVID-19 pandemic: Consensus statement of the International League against epilepsy and the International Federation of Clinical Neurophysiology. Issue 9 (September 2021) - Beniczky, Sándor; Husain, Aatif; Ikeda, Akio; Alabri, Haifa; Helen Cross, J.; Wilmshurst, Jo; Seeck, Margitta; Focke, Niels; Braga, Patricia; Wiebe, Samuel; Schuele, Stephan; Trinka, Eugen
Highlights: The COVID-19 pandemic has led to lockdown of many Epilepsy Monitoring Units. Postponing video-EEG monitoring of patients had detrimental effects. Access to video-EEG monitoring be given high priority. Abstract: Restructuring of healthcare services during the COVID-19 pandemic has led to lockdown of Epilepsy Monitoring Units (EMUs) in many hospitals. The ad-hoc taskforce of the International League Against Epilepsy (ILAE) and the International Federation of Clinical Neurophysiology (IFCN) highlights the detrimental effect of postponing video-EEG monitoring of patients with epilepsy and other paroxysmal events. The taskforce calls for action to continue functioning of Epilepsy Monitoring Units during emergency situations, such as the COVID-19 pandemic. Long-term video-EEG monitoring is an essential diagnostic service. Access to video-EEG monitoring of the patients in the EMUs must be given high priority. Patients should be screened for COVID-19, before admission, according to the local regulations. Local policies for COVID-19 infection control should be adhered to during the video-EEG monitoring. In cases of differential diagnosis where reduction of antiseizure medication is not required, consider home video-EEG monitoring as an alternative in selected patients.